Impact on postoperative complications of changes in skeletal muscle mass during neoadjuvant chemotherapy for gastro‐oesophageal cancer. Issue 5 (25th August 2020) - den Boer, R. B.; Jones, K. I.; Ash, S.; van Boxel, G. I.; Gillies, R. S.; O'Donnell, T.; Ruurda, J. P.; Sgromo, B.; Silva, M. A.; Maynard, N. D.
Abstract : Background: Risk assessment is relevant to predict postoperative outcomes in patients with gastro‐oesophageal cancer. This cohort study aimed to assess body composition changes during neoadjuvant chemotherapy and investigate their association with postoperative complications. Methods: Consecutive patients with gastro‐oesophageal cancer undergoing neoadjuvant chemotherapy and surgery with curative intent between 2016 and 2019 were identified from a specific database and included in the study. CT images before and after neoadjuvant chemotherapy were used to assess the skeletal muscle index, sarcopenia, and subcutaneous and visceral fat index. Results: In a cohort of 199 patients, the mean skeletal muscle index decreased during neoadjuvant therapy (from 51·187 to 49·19 cm 2 /m 2 ; P < 0·001) and the rate of sarcopenia increased (from 42·2 to 54·3 per cent; P < 0·001). A skeletal muscle index decrease greater than 5 per cent was not associated with an increased risk of total postoperative complications (odds ratio 0·91, 95 per cent c.i. 0·52 to 1·59; P = 0·736) or severe complications (odds ratio 0·66, 0·29 to 1·53; P = 0·329). Conclusion: Skeletal muscle index decreased during neoadjuvant therapy but was not associated with postoperative complications. Abstract : Deconditioning during neoadjuvant chemotherapy is a possible parameter for predicting operative outcomes. This retrospective cohort study aimed to assess body composition changes in patients with gastro‐oesophageal cancer during neoadjuvant therapy and investigate their association with postoperative complications. Skeletal muscle index values decrease during neoadjuvant therapy, but this change is not associated with postoperative complications. Does not predict risk of complications Abstract : Antecedentes: La evaluación de riesgo es importante para predecir los resultados postoperatorios en pacientes con cáncer gastroesofágico. Este estudio de cohortes tuvo como objetivo evaluar los cambios en la composición corporal durante la quimioterapia neoadyuvante e investigar su asociación con complicaciones postoperatorias. Métodos: Los pacientes consecutivos con cáncer gastroesofágico sometidos a quimioterapia neoadyuvante y cirugía con intención curativa entre 2016 y 2019, identificados a partir de una base de datos específica, se incluyeron en el estudio. Se utilizaron las imágenes de tomografía computarizada, antes y después de la quimioterapia neoadyuvante, para evaluar el índice de masa muscular esquelética, la sarcopenia y el índice de grasa visceral y subcutánea. Resultados: En una cohorte de 199 pacientes, el índice de masa muscular esquelética disminuyó durante el tratamiento neoadyuvante (de 51, 87 cm 2 /m 2 a 49, 19 cm 2 /m 2, P < 0, 001) y las tasas de sarcopenia aumentaron (de 42, 2% a 54, 2%, P < 0, 001). Una disminución del índice de masa muscular esquelética > 5% no se asoció con un mayor riesgo de complicaciones postoperatorias globales (razón de oportunidades, odds ratio : 0, 908; ic. del 95%: 0, 520‐1, 587, P = 0, 736) ni de complicaciones graves ( odds ratio : 0, 661; i.c. del 95%: 0, 286‐1, 525, P = 0, 329). Conclusión: El índice de masa muscular esquelética disminuyó durante el tratamiento neoadyuvante, pero no se asoció con complicaciones postoperatorias.